Quality recognition and prediction smarter pattern technology with the Mahalanobis-Taguchi system - Teshima, Shoichi; Hasegawa, Yoshiko; Tatebayashi, Kazuo (Momentum Press, 2012)
The Mahalanobis-Taguchi data handling and pattern recognition system is widely established-- built and extended from the original quality control precepts of Genichi Taguchi. But the MT system is not always well understood. This new book makes the system much more vivid and concrete with real-life applications in a wide variety of disciplines from industry to general commerce. The book offers a clear computational method to show the user how to actually apply the system to real manufacturing control problems. With the renowned international industry background of the three authors and their historic ties to Genichi Taguchi, this book will bring a unique insight into how to get the most benefits from the MT System. The book offers an overview of pattern recognition issues and the precepts of the MT system. explains the merits of the MT System and its computational methods. shows how to handle data with the MT System and extract useful information. provides a useful comparison of the advantages and disadvantages between traditional Artificial Intelligence systems and the MT system. provides case study examples of MT Systems applications.